Determinan Ekonomi Pada Perilaku Picky Eater Anak Usia 1-3 (Toddler) Tahun di KB Al-Qodiriyah Banyuwangi - Maria Qori’ah; Khusnul Khotimah; Rifka Taufiqur Rofiah (Institut Agama Islam Nahdlatul Ulama Tuban, 2023)
Children are the most precious fruit. Always monitoring growth and development is the main thing for parents. Picky eaters or what is usually called difficulty eating and having the behavior of eating easily full, eating slowly, fussy behavior and being too picky about food and having a lack of response to food are one of the problems faced by many parents of children aged 1-3 years. or called toddler. The causal factors can occur from various economic and social aspects. This research aims to determine the existence of economic factors in children who are picky eaters aged 1-3 years or toddlers at the Al-Qodiriyah Banyuwangi KB. This research method uses quantitative research with a cross sectional approach with a population of all children's parents. The sampling technique used simple random sampling of 20 parents. The data collection tool uses a questionnaire that is given to parents to answer. Data analysis is the result of interpretation of the chi-square test with a p-value of 0.170>0.05, which shows that there is no influence of economic factors in terms of the occupation of parents who are not employees such as farmers or traders. A parent's income of less than IDR 1,500,000 does not make a child a picky eater. The decreasing poverty rate in Banyuwangi is a clear manifestation that the community has high consumptive power to be able to provide food that meets balanced nutrition.